(untitled) (Progressive Agriculture, 2017)
Moisture content is one of the most important factors determining grain quality during harvesting, storage, trading, processing, and transportation because high moisture will create problems for farmers, especially during postharvest activities such as mold growth, higher insect infestation, loss in seed germination, and low market price. A study was conducted to find out a precise moisture meter (MM) for moisture content (MC) determination during post-harvest activities of rice. John Deere moisture meter (JD MM), Moisture Probe and RiceterL MM were tested and calibrated to provide accurate result compared to that of Oven dry method. The average MC of same samples was found 11.4, 11.8, 12.3, and 13.1% by Oven dry method, Moisture Probe, RiceterL and John Deere MM, respectively. Standard deviations of the mean are 0.11, 0.17, 0.13 and 0.22, respectively by the corresponding moisture meters. Oven dry method i.e. drying whole kernels for 72 h at 105°C had the smallest standard deviation. This indicated long drying time and adequate drying temperature could ensure the precision of moisture determination. The reading of John Deere, Moisture Probe and RiceterL MM is higher by 1.7, 0.4 and 0.9%, respectively than that of oven dry method. Moisture measurement by these methods can lead to wide variations of conclusion. Moisture measurement by John Deere moisture meter is quicker and easier than Moisture Probe and RiceterL (MM). However, adjustment procedure with respect to calibration is needed before use. Progressive Agriculture 27 (4): 511-516, 2016